2020
DOI: 10.1055/a-1286-2917
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment Landscape and Prognosis After Treatment with Trastuzumab Emtansine

Abstract: Purpose Pertuzumab and T-DM1 are two efficient anti-HER2 treatments for patients with HER2-positive advanced breast cancer. While pertuzumab is usually given in first-line treatment and T-DM1 in second-line treatment, standard therapy options seem to be exhausted up to now after the treatment of patients with these two therapy options. Therefore, it is important to have data that describes the therapy situation and prognosis after T-DM1 treatment. Methods The PRAEGNANT metastatic breast cancer regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…The latest clinical trials that studied resistance mechanisms to anti-HER2 therapies have revealed positive prognostic improvements, suggesting the necessity of additional trials in patients who have a high probability of benefitting from further anti-HER2 treatments. 36…”
Section: Discussionmentioning
confidence: 99%
“…The latest clinical trials that studied resistance mechanisms to anti-HER2 therapies have revealed positive prognostic improvements, suggesting the necessity of additional trials in patients who have a high probability of benefitting from further anti-HER2 treatments. 36…”
Section: Discussionmentioning
confidence: 99%
“…Die Studie Prospective Academic Translational Research Network for the Optimization of the Oncological Health Care Quality in the Adjuvant and Advanced/Metastatic Setting (PRAEGNANT, NCT02 338 167 31 ) ist ein laufendes prospektives Brustkrebsregister mit einem Dokumentationssystem, das dem in klinischen Studien verwendeten ähnelt. Die Ziele von PRAEGNANT bestehen darin, die Behandlungsmuster und Lebensqualität zu bewerten sowie Patienten zu identifizieren, die für klinische Studien oder spezifische gezielte Behandlungen in Frage kommen 31 32 33 34 35 . Die Patienten können zu jedem Zeitpunkt ihres Krankheitsverlaufs einbezogen werden.…”
Section: Patienten Und Methodenunclassified
“…The Prospective Academic Translational Research Network for the Optimization of the Oncological Health Care Quality in the Adjuvant and Advanced/Metastatic Setting study (PRAEGNANT, NCT02338167 31 ) is an ongoing prospective breast cancer registry with a documentation system similar to that used in clinical trials. The aims of PRAEGNANT are to assess treatment patterns and quality of life and to identify patients who may be eligible for clinical trials or specific targeted treatments 31 , 32 , 33 , 34 , 35 . Patients can be included at any point during the course of their disease.…”
Section: Methodsmentioning
confidence: 99%